The Effectiveness of Self-Compassion Based Therapy on the Idealism and Attachment Styles in Secondary High School Female Students with Generalized Anxiety Disorder - MOHAMMAD ORAKI; mozhgan bitaneh (Ravānshināsī-i Afrād-i Istis̠nāyī, 2020)
Generalized anxiety disorder can be followed by numerous psychological and emotional damages for the students that appropriate psychological therapies should be applied to treat this disorder. therefore the present study was conducted aiming to investigate the effectiveness of self-compassion-based therapy on the idealism and attachment styles in secondary high school female students with generalized anxiety disorder? it was a quasi-experimental study with pretest, posttest with control group. The statistical population of the current study was secondary high school female students with generalized anxiety disorder in zone 14 Tehran in academic year 2018-19. 30 high school female students with generalized anxiety disorder were selected through purposive sampling method and they were randomly accommodated into experimental and control groups (each group of 15). The experimental group received self-compassion-based therapy intervention (Gilbert, 2009) during two-and-a-half months in ten seventy-five-minute sessions. The applied questionnaires in this study included generalized anxiety disorder questionnaire (Spitzer, et.al, 2006) and idealism (Hill et.al, 2004) and attachment styles questionnaire (Collins and Reed, 1990). The data from the study were analyzed through MANCOVA method. the results showed that self-compassion-based therapy has had significant effect on the idealism and anxiety, safe and avoidant attachment styles in secondary high school female students with generalized anxiety disorder (p < 0.001)